Strategi Pemantauan Kualitas Air Bersih pada Rumah Tangga Miskin di Kampung Holtekamp, Kota Jayapura, Papua - Gaspar Bao Balabuana; Raynard C. Sanito; Alfred B. Alfons (Fakultas Teknik, 2023)
Jayapura City is an indicator of Papua's development in general. In 2012, the city of Jayapura had 25,653 poor households, with a total population of 102,612. Muara Tami District is a district with a total number of households that reaches 86.6%. The highest population density is in Muara Tami district, located in Holtekamp village with a total of 243 households. Clean water quality includes physical, chemical and biological parameters. Determination of precise parameters based on pollutant sources and determination of sampling points, as well as the weather are effective means of cost-efficiency in air quality monitoring. The results of the analysis show that the dug wells of Holtekamp village residents are in the category of heavy pollution. Most of the physical - chemical - biological conditions of the air did not meet the class I air quality standards. The lowest COD value was 25 mg / L and reached 35 mg / L, as well as the lead content (Pb), the lowest was 0.035 mg/L and the highest was 0.37. mg / L, while the lowest E. Coli content was 29 MPN / 100 mL and the highest was 390 MPN / 100 mL. This is due to poor sanitation and construction of dug wells. Keywords: Holtekamp, dug wells, water pollution